2019
DOI: 10.1093/humrep/dez066
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of two guided self-administered interventions for psychological distress among women with infertility: a three-armed, randomized controlled trial

Abstract: STUDY QUESTION What is the effect of two guided self-administered interventions on psychological distress in women undergoing IVF or ICSI? SUMMARY ANSWER A brief mindfulness intervention significantly reduced depression and improved sleep quality, while the gratitude journal intervention showed no significant effect on any outcome variables. WHAT IS KNOWN ALREADY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 65 publications
1
26
0
1
Order By: Relevance
“…Al 2015(31) the controls received an introductory letter and instructions on how to complete questionnaires.Two studies were three-armed RCTs(37,38). Bai et al(37) had two intervention groups; a Brief Mindfulness Group (BMG) and Gratitude Journal Group (GJG), and one control group. Outcome data from both intervention groups were included in the meta-analysis.…”
mentioning
confidence: 99%
“…Al 2015(31) the controls received an introductory letter and instructions on how to complete questionnaires.Two studies were three-armed RCTs(37,38). Bai et al(37) had two intervention groups; a Brief Mindfulness Group (BMG) and Gratitude Journal Group (GJG), and one control group. Outcome data from both intervention groups were included in the meta-analysis.…”
mentioning
confidence: 99%
“…The ESHRE Infertility Declaration recommended that infertility centers should provide psychosocial and emotional support for patients (24). In a recent randomized controlled trial, brief mindfulness intervention has been reported to reduce depression and improve sleep quality in infertile patients (25).…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of 3,522 adult patients from published parallel 29 RCTs (Sarrel and DeCherney, 1985;Domar et al, 2000a,b;Hosaka et al, 2002;Emery et al, 2003;Shu-Hsin, 2003;de Klerk et al, 2005;Chan et al, 2006Chan et al, , 2012Tuil et al, 2007;Cousineau et al, 2008;Faramarzi et al, 2008;Mori, 2009;Haemmerli et al, 2010;Sexton et al, 2010;Matthiesen et al, 2011a;Skiadas et al, 2011;Gorayeb et al, 2012;Mosalanejad et al, 2012a,b;Domar et al, 2015;Vizheh et al, 2013;Arslan-Özkan et al, 2014;van Dongen et al, 2016;Frederiksen et al, 2017;Nery et al, 2018;Bai et al, 2019;Sahraeian and Lotfi, 2019;Hosseini et al, 2020) were described in the study. The average age ranged from 20 to 40 years.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…A variety of psychotherapy interventions, including CBT (Domar et al, 2000a,b;Hosaka et al, 2002;Shu-Hsin, 2003;Faramarzi et al, 2008;Haemmerli et al, 2010;Sexton et al, 2010;Gorayeb et al, 2012;Mosalanejad et al, 2012a,b;Domar et al, 2015;Sahraeian and Lotfi, 2019), the BMS (Chan et al, 2006(Chan et al, , 2012, and other treatments (Sarrel and DeCherney, 1985;Domar et al, 2000a,b;Emery et al, 2003;de Klerk et al, 2005;Tuil et al, 2007;Cousineau et al, 2008;Mori, 2009;Matthiesen et al, 2011a;Skiadas et al, 2011;Vizheh et al, 2013;Arslan-Özkan et al, 2014;van Dongen et al, 2016;Frederiksen et al, 2017;Nery et al, 2018;Bai et al, 2019;Hosseini et al, 2020), were included in the meta-analysis. Sixteen studies (Shu-Hsin, 2003;de Klerk et al, 2005;Chan et al, 2006Chan et al, , 2012Tuil et al, 2007;Sexton et al, 2010;Matthiesen et al, 2011a;Skiadas et al, 2011;Gorayeb et al, 2012;Mosalanejad et al, 2012a,b;Domar et al, 2015;van Dongen...…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%